Capillary electrophoresis coupled to contactless conductivity detection for analysis of amino acids of agricultural interest in composting. Issue 19 (October 2016) - Cappelini, Luciana Teresa Dias; de Fátima Menegoci Eugênio, Patrícia; Leãao, Paulo Augusto Gomes Carneiro; Alberice, Juliana Vieira; Urbaczek, Ana Carolina; Assunçãao, Nilson Antonio; Juliano, Luiz; Carrilho, Emanuel
Abstract : Electrophoresis 2016, 37, 2449–2457. DOI:10.1002/elps.201600302 If an average household produces weekly several pounds of organic garbage, imagine the volume of a large zoo like São Paulo Zoo. The amount of organic waste, from feeding left overs, to plants, manure and even dead animals, is enough to produce up to 120 tons monthly. If all this organic matter was sent to dumping grounds, this would create a serious environmental problem. Composting is a sustainable approach by the São Paulo Zoo to manage animal and vegetal waste generated in the Zoo's premises. The resulting compost is often used as organic fertiliser for the production of vegetables, which is further used to feed the animals. The compost produced provides many forms of minerals and also amino acids (AA) that are used by plants as nutrients. Since most amino acids absorb only slightly or not at all in the UV wavelengths, we developed a method for the determination of AA of agricultural interest in the compost samples. Due to the complexity of these samples, we used ion exchange chromatography for purification of AA prior analysis. The proposed CZE‐C4Dmethod allowed a separation of the AA in a short analysis time (less than 3.0 min) without the need for derivatization, with sensitivity and reproducibility suitable for such samples. Photograph: Paulo Gil